Is the Anthropocene really worthy of a formal geologic definition? - Certini, G.; SCALENGHE, Riccardo (The Anthropocene Review, 2014)
Scientists are actively debating whether the Anthropocene, the geologic time span (GTS) we are now living in, should be considered a period, epoch, or age in the geologic timescale. The solution is not easy, because the beginning of this GTS is undefined and the end unknown. In fact, there is no agreement on when the Anthropocene began, the proposed dates ranging from the Second World War, when radioactive fallout branded soils and sediments all over the world, to little after the end of the last glacial period, i.e. 11.7 thousand years ago, therefore coinciding with the onset of the Holocene. We are in favour of a concurrence of the Anthropocene with the Holocene, although a major impact of people on the environment began diachronically in different parts of the world. This single GTS should be named Anthropocene because it is chiefly characterized by a peculiar process of change for the planet: human impact. Nevertheless, a pivotal hindrance for the Anthropocene to be worthy of a formal geologic definition remains. The Anthropocene is open ended, therefore its real duration is unknown.